Pengaruh Penggunaan Media Pembelajaran Flash Card pada Materi Sistem Pencernaan Manusia terhadap Hasil Belajar - Nurul Lathifah (Tadris Biologi, Tadris Fisika and Tadris Kimia, Universitas Islam Negeri Antasari, 2023)
This study aims to determine how student learning outcomes on the material of the human digestive system class XI SMA Al Munawwir Tamban use flash card media. The design of this study used a pre-experimental research design with the type of One-Group Pretest-Posttest Design. The sample in this study used one class of 16 students. The treatment in this class is divided into two, namely by using flash card media and not using flash card media. The instrument given is in the form of a test instrument which consists of 30 multiple choice questions. The results showed that in the t-test the t-table value was 2.131, thus the t-count value was 15.800> 2.131, then the t-count value with t-table, it can be concluded that H0 is rejected and H1 is accepted, which means that there is an average difference between the pretest learning outcomes. with posttest, which means that there is an effect of using flash card media on Biology learning outcomes in class XI SMA Al Munawwir Tamban. Keywords: Flash card, learning outcomes.